PSYCHOLOGICAL CONTRACT FULFILMENT AND WELL-BEING - Ahmad, Mohamad Irwan; Firman, Kirsty Paul; Smith, Hugo Paul; Smith, Andrew Paul (Advances in Social Sciences Research Journal, 2018)
Background There is considerable literature on well-being at work, the well-being process and short measures of psychosocial concepts. Psychological Contract Fulfilment (PCF) and other employee attitudes and behaviours have also been widely studied. Aims and objectives The aim of the present study was to examine associations of short measures of PCF and well-being outcomes while statistically adjusting for other established predictors (job characteristics, coping styles and personality). Methods The survey included established measures of well-being and the newly developed PCF short items. The questions were presented in an online survey, delivered using Qualtrics software and given to 166 workers from the USA, who were recruited using Mechanical Turk. Results Factor analyses identified the following measures: negative job characteristics; positive work characteristics; positive and negative coping; positive personality; PFC; work behaviours and job attitudes; work-life balance; and positive and negative well-being. While the PFC variables were significantly associated with well-being outcomes in univariate analyses, these effects were no longer significant when established predictors were included in the analyses. Conclusion Effects attributed to PFC may reflect other organisational and individual variables. The new short items can be used in future studies of the well-being of workers. This will lead to an increase in our knowledge and the development of new models that can be of theoretical and practical significance.